2010
DOI: 10.5387/fms.56.91
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Factors for the Resorption of a Lumbar Disc Herniation on Plain Mri

Abstract: : Previous studies have noted the morphologic changes of lumbar disc herniation (LDH) in conservative treatment and predictive value of the resorption of LDH by using contrast -enhanced MRI. However, there are few reports that note the predictive value of plain, non -enhanced MRI. Therefore, no definite predictive factors for the resorption of LDH have been detected on plain MRI. Thirty -four patients with lower limb pain receiving conservative treatment were followed for more than 6 months. MRI was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…While modic change was not recognized as a predictive factor of resorption in this study, a 2014 study by Shan et al reported that whereas 35 of 85 patients in the modic change group (of whom the majority were of Type 2) did not show much difference in IDH size, the group with no modic change displayed significant decrease [32]. Iwabuchi et al purported that resorption factors could be identified on T1- and T2-weighted MRIs, with high signal intensity of IDH areas in T1- and T2-weighted MRIs in the nonregression group [33]. …”
Section: Discussionmentioning
confidence: 99%
“…While modic change was not recognized as a predictive factor of resorption in this study, a 2014 study by Shan et al reported that whereas 35 of 85 patients in the modic change group (of whom the majority were of Type 2) did not show much difference in IDH size, the group with no modic change displayed significant decrease [32]. Iwabuchi et al purported that resorption factors could be identified on T1- and T2-weighted MRIs, with high signal intensity of IDH areas in T1- and T2-weighted MRIs in the nonregression group [33]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many patients do present LDH or other degenerative changes in an MRI of their lumbar spine without any related clinical symptoms 1,6,7 and that other neurogenic, musculoskeletal, immunogenic, or neoplastic diseases can mimic clinical symptoms of LDH. [8][9][10] Thus, a clinician can never be entirely sure if an LDH in a patient's MRI with ''radicular-like'' pain is the source for the patient's pain, or if there is another pathology that generates the patient's pain.…”
Section: Discussionmentioning
confidence: 99%
“…The technique was described in former reports and showed good inter-and intraobserver reliability. 1,4 SI of nucleus pulposus was determined by forming the mean of SI of anterior, median, and posterior part of each nucleus pulposus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al [12] studied the spinal canal morphology of 182 patients whose symptoms were signi cantly relieved after conservative or surgical treatment, and found that the spinal canal volume in the patients in the conservative treatment group was signi cantly greater than of the patients in the surgery group. On the basis of the different signal characteristics of protrusions on ordinary MRI, Iwabuchi et al [13] speculated that most type 1 protrusions were composed of nucleus pulposus. A nucleus pulposus with high water content and a small degree of degeneration was more likely to show vascular growth and tissue dehydration, factors realizing the resorption of protrusions.…”
Section: Introductionmentioning
confidence: 99%